Pengembangan Pariwisata Berbasis Masyarakat (Community Based Tourism) dalam Pengelolaan Desa Wisata di Kenagarian Pariangan - Santi Yutaro, Silvia; Jumiati, Jumiati (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to determine community-based tourism development in managing tourist villages in Kenagarian Pariangan. This research was conducted using a qualitative approach with descriptive methods. Data was collected through interviews and observation, and documentation was analyzed using data reduction, data presentation, and verification techniques. The results showed that community-based tourism positively impacted economic and cultural aspects but was not optimal in the environmental and political dimensions. However, in implementing the concept of community-based tourism (CBT) in tourism development in the tourist village of Kenagarian Pariangan, the community is still not optimal in developing tourist areas with the concept of community-based tourism development. The main obstacles include internal factors such as human resources, facilities, and budgets and external factors such as environmental conditions and existing regulations. Efforts that can be made include increasing public awareness, active participation in tourism management, and education about local tourism potential.